2022
DOI: 10.1088/1742-6596/2157/1/012046
|View full text |Cite
|
Sign up to set email alerts
|

The Science Environment Technology Society (SETS) based e-module development with project based learning model in colloidal learning

Abstract: Online learning prefers to use electronic teaching materials, one of the teaching materials used is e-modules as a learning resource that can improve students’ abilities. This form of inquisition is oriented to R&D (Research & Development) with the application of the ADDIE model (Analysis, Design, Development, Implementation, Evaluation). Research for implementation of e-module based using pre-experiment design with One Group Pretest-Posttest Design. The sample selection was done by purposive sampling … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 25 publications
0
1
0
Order By: Relevance
“…34 The interpretation of the criteria in this study is different from Andila's research which showed the results of student responses to physics e-modules of 80.59% in the practical category. 35…”
Section: Implementing Stagementioning
confidence: 99%
“…34 The interpretation of the criteria in this study is different from Andila's research which showed the results of student responses to physics e-modules of 80.59% in the practical category. 35…”
Section: Implementing Stagementioning
confidence: 99%